Utamaro - Goncourt, Edmond de, 1822-1896 (Temporis collection., 2012)
If sensuality had a name, it would be without a doubt Utamaro. Delicately underlining the Garden of Pleasures that once constituted Edo, Utamaro, by the richness of his fabrics, the long necks of swans, the mysterious looks, evoke in a few lines the sensual pleasure of the Orient. If some scenes betray discreetly lovers' games, a great number of his shungas recall that love in Japan is first and foremost erotic.